1986
DOI: 10.1126/science.3529392
|View full text |Cite
|
Sign up to set email alerts
|

Prorenin in High Concentrations in Human Ovarian Follicular Fluid

Abstract: Although the kidney is a major source of prorenin, the precursor of renin, there are extrarenal sources for plasma prorenin that have not been identified. The selective increase in plasma prorenin at the time of ovulation suggested that one of these sources might be the ovary. Prorenin was therefore measured in fluid aspirated from 18 ovarian follicles and in plasma collected from three women who were undergoing in vitro fertilization. The follicular fluid contained high concentrations of prorenin that were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
3

Year Published

1991
1991
2000
2000

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(86 citation statements)
references
References 21 publications
4
79
0
3
Order By: Relevance
“…Most other tissues that have been found to express the renin gene apparently release only prorenin [ 12,14,[20][21][22][23][24][25][26][29][30][31]. These data could imply that the prorenin processing enzyme has a highly restricted tissue distribution; however, the prorenin synthesized by the transfected AtT-20 cells was cleaved to active renin at the natural cleavage site (documented by amino terminal sequencing), and the release of renin was regulated by the same stimulus (cAMP; in this case, 8Br-cAMP) that promotes the release of renal renin [32].…”
Section: Post-transcriptional Events In Renin Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most other tissues that have been found to express the renin gene apparently release only prorenin [ 12,14,[20][21][22][23][24][25][26][29][30][31]. These data could imply that the prorenin processing enzyme has a highly restricted tissue distribution; however, the prorenin synthesized by the transfected AtT-20 cells was cleaved to active renin at the natural cleavage site (documented by amino terminal sequencing), and the release of renin was regulated by the same stimulus (cAMP; in this case, 8Br-cAMP) that promotes the release of renal renin [32].…”
Section: Post-transcriptional Events In Renin Gene Expressionmentioning
confidence: 99%
“…Whereas most investigators have concluded that there is no conversion of prorenin to renin in the circulation [1,12,14,15], it has been reported that the rat kidney releases a protease that cleaves renin in the circulation [39]. Others have proposed that prorenin might have in vivo activity, for example, through reversible activation or after its uptake by peripheral tissues [ 12,21,40]. To address issues such as these, prorenin was infused into rhesus monkeys over a 40-minute period [41].…”
Section: Activity Of Infused Proreninmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, levels of Ang II-ir and of prorenin were comparable in the plasma and in the pleural liquid, while they were clearly higher in the ascites, even though ascites and pleural fluid displayed a similar total protein count. Our present observation provides additional support for the ovarian origin of prorenin and Ang IIir in the ascites of OHSS, given the existence of an ovarian RAS able to produce prorenin locally (9) and Ang II (10) and the stimulatory role of gonadotropins on this local system (11). In patient 2, levels of prorenin and Ang II-ir were slightly higher in the pleural fluid than in the plasma.…”
Section: Discussionmentioning
confidence: 84%
“…In this regard, the correction of abdominal ascites by a chest tube placed to drain pleural effusion has been reported recently in a patient with severe OHSS (12). Plasma levels of renin activity, active renin, prorenin, and Ang II-ir were clearly higher than those observed in patients stimulated with gonadotropins for IVF on the day of oocyte retrieval (9)(10)(11)13), suggesting peripheral stimulation of the RAS during OHSS. Active renin was measured by an immunoradiometric assay.…”
Section: Discussionmentioning
confidence: 99%